Estimation of Shelf Life of Sambal Payangka Fish (Ophiocara porocephala) Using Different Types of Packaging with Accelerated Shelf-Life Testing (ASLT) Method - Bungi, Nur'Ivani Mus; Bait, Yoyanda; Liputo, Siti Aisa (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
Payangka fish sambal, made from payangka fish, the one endemic fish from Gorontalo. This research aims to use the Accelerated Shelf-Life Test (ASLT) method with the Arrhenius model to measure shelf life of sambal. This method includes treating several types of packaging: plastic bottles (A1), glass bottles (A2), and standing pouches with aluminum foil (A3). The quality assessment was carried out using peroxide and organoleptic levels, as well as aroma. During three days of storage, a decrease in the quality was observed at temperatures of 35 °C, 45 °C, and 55 °C, with observations made every twenty-four hours. The results showed that the peroxide levels increased during storage, ranging from 2.53-4.12 mEqO2 /kg for plastic packaging, 2.33-3.18 mEqO2 /kg, for glass bottles, and 2.40-3.86 mEqO2 /kg for standing pouches with aluminum foil. Additionally, the organoleptic test for payangka fish aroma showed a decrease in panelist ratings, ranging from better to worse. The Arrhenius model calculations showed that peroxide levels are important in determining shelf life of payangka fish sambal. When tested at room temperature (25 °C - 30 °C), payanga fish sambal stored in glass bottles exhibited a relatively longer shelf life. Specifically, at a temperature of 25 °C, shelf life ranged from 68 days to 48 days at 30 °C.